AcOTApks Gene-Based Molecular Tools to Improve Quantitative Detection of the Mycotoxigenic Fungus Aspergillus carbonarius - Angelo Agnusdei; Rita Milvia De Miccolis Angelini; Francesco Faretra; Stefania Pollastro; Donato Gerin (Foods)
Ochratoxin A (OTA) is a mycotoxin, a common contaminant of grapes and their derivatives, such as wine, and classified as possible human carcinogen (group 2B) by the International Agency for Research on Cancer (IARC). Aspergillus carbonarius is the main producer of OTA in grapes. The stability of the molecule and the poor availability of detoxification systems makes the control of A. carbonarius in vineyards the main strategy used to reduce OTA contamination risk. Several molecular methods are available for A. carbonarius detection, but the correlation between the abundance of fungal population and OTA contamination needs to be improved. This study aimed at the development of innovative quantitative PCR (qPCR) and digital droplet PCR (ddPCR) tools to quantify the mycotoxigenic fractions of A. carbonarius strains on grapes, based on the key gene AcOTApks in the pathway of OTA biosynthesis. Different primers/probe sets were assessed, based on their specificity and sensitivity. This method allowed to quantify up to 100 fg∙µL−1 [cycle of quantification (Cq) = 37] and 10 fg∙µL−1 (0.38 copies∙µL−1) of genomic DNA (gDNA) from A. carbonarius mycelium in qPCR and ddPCR, respectively. The sensitivity as to artificially contaminated must samples was up to 100 conidia (Cq = 38) and 1 conidium (0.13 copies∙µL−1) with qPCR and ddPCR, respectively. Finally, the methods were validated on naturally infected must samples, and the quantification of the fungus was in both cases highly correlated (r = +0.8) with OTA concentrations in the samples. The results showed that both analytical methods can be suitable for improving the sustainable management of OTA contamination in grapes and their derivatives.